Food aid and sustainable livelihoods: BRAC's innovations against hunger - Sattar, M. Ghulam; Chowdhury, Nusrat Sabina; Hossain, Md. Altaf (BRAC Research and Evaluation Division (RED), 2020)
The study aims to examine the situation of the poor in Bangladesh and analyse the experiences of BRAC in ensuring food security for the extreme poor through its two specially designed programmes: (a) Income Generation for Vulnerable Groups Development (IGVGD), and (b) Agroforestry. The programmes are the outcome of an urgent search for innovations against hunger. Both the programmes stemmed from food-aid initiatives. Both the programmes stemmed from food-aid initiatives and are targeted to vulnerable women. The fmdings are based on the perceptions of the programme participants who are members of organised groups of food insecure women, and other stakeholders of the food-aid programmes, i.e. elected chairmen of Union Parishad, officials of related government departments, and local representatives of international development partners. Programme records and reports of some empirical studies related to IGVGDP were also consulted. Focus group discussion (FGD) was used as a method of capturing the perceptions of the women participating in the two programmes. 97 women of IGVGD programme and 30 women members associated with the Agroforestry took part in different FGD sessions. Information from others were gathered through in-depth interviews.